The Library Ladies of Clay Center: Clay County, Kansas, 1898 - Harrell, Mallory (Kansas State University, The Chapman Center for Rural Studies, 2017)
This exhibition covers the history of The Clay Center Library Club, based out of Clay Center in Clay County Kansas. The Club was a charter of the General Federation of Women’s Clubs and were responsible for many efforts to promote education, service work and self-improvement in their local community. Their most famous project was the organization of the erection of Clay Center Carnegie Library, pictured above, that continues to serve the community to this day. This study relies on club records, local histories, and newspapers and online resources.
Mallory Harrell, “The Library Ladies of Clay Center: Clay County, Kansas, 1898,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/243.
Keywords: Carnegie Library; Literary Clubs; Clay Center; Self-Improvement; Camp Funston; Matfield Green